Three-Dimensional Modeling and Augmented Reality and Virtual Reality Simulation of Fiber Dissection of the Cerebellum and Brainstem. Issue 5 (7th November 2022) - Gurses, Muhammet Enes; Gungor, Abuzer; Rahmanov, Serdar; Gökalp, Elif; Hanalioglu, Sahin; Berker, Mustafa; Cohen-Gadol, Aaron A.; Türe, Uğur
Abstract : BACKGROUND: Surgeons must understand the complex anatomy of the cerebellum and brainstem and their 3-dimensional (3D) relationships with each other for surgery to be successful. To the best of our knowledge, there have been no fiber dissection studies combined with 3D models, augmented reality (AR), and virtual reality (VR) of the structure of the cerebellum and brainstem. In this study, we created freely accessible AR and VR simulations and 3D models of the cerebellum and brainstem. OBJECTIVE: To create 3D models and AR and VR simulations of cadaveric dissections of the human cerebellum and brainstem and to examine the 3D relationships of these structures. METHODS: Ten cadaveric cerebellum and brainstem specimens were prepared in accordance with the Klingler's method. The cerebellum and brainstem were dissected under the operating microscope, and 2-dimensional and 3D images were captured at every stage. With a photogrammetry tool (Qlone, EyeCue Vision Technologies, Ltd.), AR and VR simulations and 3D models were created by combining several 2-dimensional pictures. RESULTS: For the first time reported in the literature, high-resolution, easily accessible, free 3D models and AR and VR simulations of cerebellum and brainstem dissections were created. CONCLUSION: Fiber dissection of the cerebellum-brainstem complex and 3D models with AR and VR simulations are a useful addition to the goal of training neurosurgeons worldwide.